Climate Changes between 25,000 and 6,000yrsBP Deduced from TOC, TN, and Fossil Pollen Analyses of a Sediment Core from Lake Nojiri, Central Japan - 公文, 富士夫; 河合, 小百合; 井内, 美郎
1988年に野尻湖湖底から採取されたオールコア試料の上部について, 30～50年間隔の精度で有機炭素(TOC) ･全窒素(TN)の測定と花粉分析を行った.4点の¹⁴C年代測定,鬼界アカホヤ(K-Ah)および姶良Tn(AT)の指標火山灰年代に基づいて推定した堆積年代と, TOC･TNおよび花粉の分析結果に基づくと,遅くとも¹⁴C年代で1.4～1.5万年前より前には落葉広葉樹花粉の増加で示されるような温暖化が始まり,以後, ｢寒の戻り｣を伴いながら約1万年前まで温暖化が進行した.約1.3万年(較正年代1.5万年前)前後には, ｢寒の戻り｣を示す亜寒帯針葉樹花粉の明瞭な増加が認められる.約1.2万年前(較正年代1.4万年前)には,広葉樹花粉の急増と針葉樹花粉の激減があり,同時に全有機炭素･窒素量の激増も認められ,短期間のうちに急激に温暖化が進行したと推定される.なお, ¹⁴C年代で約1.45万年前にも微弱な広葉樹花粉の減少が認められる.これらの気候変動のパターンは,北大西洋地域の気候イベント(新旧ドリアス期など)とよく似ているが,本稿における編年に基づけば,北大西洋地域よりもそれぞれ2,000～3,000年ほど古いようにみえる.較正年代で約1.3万年前と9千年前においても,軽微な気候変動が認められ,そのうちの後者はボレアル期に対比できる. Total organic carbon (TOC), total nitrogen (TN), and fossil pollen compositions have been measured at 1- to 2-cm intervals for the upper part of an all-core sample recovered from Lake Nojiri in 1988. TOC and TN contents rapidly increase from the depth zone of 610 to 540cm, with one reversal. The fossil pollen of cool-temperate deciduous trees also becomes abundant around this horizon. Subarctic conifers decrease from 730 to 540cm depth, with some fluctuations. Judging from these results and sediment ages estimated with ¹⁴C dates and some marker tephras, the Last Glacial Maximum is reconstructed to have been around 20,000yrsBP. A warming suggested by increasing fossil pollen of cool-temperate deciduous trees started around 15,000yrsBP and lasted until about 11,000yrsBP (about 12,000calBP), being intercalated with some cooler phases. The warming was especially accelerated around 12,000yrsBP (14,000calBP). The cool phases recognized in the Late Last Glacial Age can be compared with the three Dryas periods in Northern Europe by pattern matching, but their ages are older by about 2,000 to 3,000 years. This dis-cordance may be a key to understand the mechanism which controls short-term climate changes. A slight cooling phase is also recognized around 9,000yrsBP. This phase is characterized by decreases in TOC and TN contents, but is not so clearly seen in pollen compositions.This phase may be correlated to the Boreal period in Northern Europe. This ...